Ale, beer and brewsters in England women's work in a changing world, 1300-1600 - Bennett, Judith M. (Oxford University Press, 1996)
"Women brewed and sold most of the ale drunk in medieval England, but after 1350, men slowly took over the trade. By 1600, most brewers in London - as well as in many towns and villages - were male, not female. Ale, Beer, and Brewsters in England investigates this transition, asking how, when, and why brewing ceased to be a women's trade and became a trade of men." "Drawing on a wide variety of sources - such as literary and artistic materials, court records, accounts, and administrative orders - Judith Bennett vividly describes how brewsters (that is, female brewers) slowly left the trade. She tells a story of commercial growth, gild formation, changing technologies, innovative regulations, and finally, enduring ideas that linked brewsters with drunkenness and disorder." "Examining this instance of seemingly dramatic change in women's status, Bennett argues that it included significant elements of continuity. Women might not have brewed in 1600 as often as they had in 1300, but they still worked predominantly in low-status, low-skilled, and poorly remunerated tasks. Using the experiences of brewsters to rewrite the history of women's work during the rise of capitalism, Ale, Beer, and Brewsters in England offers a telling story of the endurance of patriarchy in a time of dramatic economic change."